Client-oriented approaches in retail bank lending - KYRYLENKO, Serhiy (Scientific journal «World of Finance», 2019)
Introduction. Crisis phenomena in the Ukrainian economy negatively affected the consumer market, caused a decrease in the population's demand for credit products of banks. However, over the past two years, an increase in the retail lending portfolio has taken place, which is evidence of a certain improvement in the socio-economic situation, the improvement of the banking system, the growth of income of citizens and the restoration of their confidence in banks. In such conditions, the task is to consolidate positive trends in retail lending, including by applying client-oriented approaches to banking.Purpose. The purpose ofthe article is to summarize the current practice of retail lending by Ukrainian banks, identify elements of client-oriented approaches in retail lending and substantiate ways to improve them.Results. The practice is analyzed and tendencies of retail lending in Ukraine are identified, the main problems that hinder its development are identified. The emphasis is on the positive impact on retail lending ofthe Law of Ukraine “On Consumer Lending”. The elements of application of client-oriented approaches in retail lending are generalized.Conclusions. The article substantiates the conclusion on how to improve client-oriented approaches in retail lending: taking into account the needs of clients in full measure; improvement of banking services; development of remote sales channels; simplification of lending conditions; increasing customer loyalty; application of stimulating tools; ensuring the availability and transparency ofbanks; distribution ofaffiiiate programs forlending.